A comprehensive review on triple R eco-management strategies to reduce, reuse and recycle of hazardous cigarette butts - Garishma Shah; Upma Bhatt; Vineet Soni (Heliyon, 2023)
Cigarettes are the globally consumed product that contributes to public health problems and is the source of the most prevalent form of litter in the world, Cigarette butts. Cigarette butts are a major source 4000 toxic chemicals, affecting the health of wildlife, humans, and the environment and their decomposition can take years due to the resistance of cellulose acetate to bacterial and fungal degradation. In 2016, the world production of cigarettes exceeded 5.7 trillion, with the majority of them consisting of cellulose acetate filters. Consequently, a massive amount of hazardous waste leaches out in the environment. Incineration and landfilling are methods of disposal, but they can result in the emission of harmful fumes and be costly. To combat this environmental issue, researchers have explored the recycling of cigarette butts in various materials, including asphalt concrete, fired clay bricks, and as a carbon source, among others. Various approaches can be used to reduce cigarette butts pollution, but efficient collection logistics by consumers remains a crucial factor for successful recycling. This paper provides innovative solutions to mitigate the cigarette butts litter problem and the feasibility of recycling methods. Despite recent progress in cigarette butts recycling solutions, there is still much room for research in this area.